Dynamic Conversation in Yoohoo and Friends Film 6th Episode at Happykids - Zainuddin Zainuddin (English Education : English Journal for Teaching and Learning, 2020)
The study aims to determine the dynamic conversation in Yoohoo and Friends film 6th Episode at Happy kids. Dynamic conversation are portrays real life of human and real communication in real social context. So, the objective of the research is to describe and to know the dynamic conversation in Yoohoo and Friends film 6th episode at happy kids. Data analysis is done by using conversation transcript. The results of the study can be concluded that the researcher found 21 conversations in Yoohoo and friends film. There are 9 Dynamic conversation within; Nonverbal, uncooperative behavior, asking explanation, asking for clarification, giving a challenge, asking for clarification, giving a challenge, asking for certainty, and giving a challenge. Moreover, Roodee has got most speech function use; it is “statement” through 24 moves. Whereas Lion has got “question” through 24 moves, and other 11 moves and they are “commands” in conversation. Over all, the researcher might suggest readers and other researchers to happily learn dynamic conversation mainly speakers’ transition in films and other media due to their own best progress understanding as well as practices English conversation.